Learning Management of Islamic Religious Education (PAI) Based on Multiple Intelligences at SMA IT Insan Mandiri Cibubur - Agus Syukur; Abuddin Nata; Dede Rosyada; Fadhilah Suralaga (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This research is entitled